2022
DOI: 10.3390/rs14133063
|View full text |Cite
|
Sign up to set email alerts
|

Applying a Wavelet Transform Technique to Optimize General Fitting Models for SM Analysis: A Case Study in Downscaling over the Qinghai–Tibet Plateau

Abstract: Soil moisture (SM) is an important land-surface parameter. Although microwave remote sensing is recognized as one of the most appropriate methods for retrieving SM, such retrievals often cannot meet the requirements of specific applications because of their coarse spatial resolution and spatiotemporal data gaps. A range of general models (GMs) for SM analysis topics (e.g., gap-filling, forecasting, and downscaling) have been introduced to address these shortcomings. This work presents a novel strategy (i.e., o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…This dataset displays high accuracy when compared with the measured data. The Daily 0.01 • × 0.01 • Land Surface Soil Moisture Dataset of the Qinghai-Tibet Plateau (2005, 2010, 2015, 2017, and 2018) was downloaded from National Tibetan Plateau Data Center [43][44][45]. This dataset was downscaled from Land Surface Soil Moisture Dataset of SMAP Time-Expanded Daily 0.25 • × 0.25 • over the Qinghai-Tibet Plateau Area.…”
Section: Reanalysis Datasetsmentioning
confidence: 99%
“…This dataset displays high accuracy when compared with the measured data. The Daily 0.01 • × 0.01 • Land Surface Soil Moisture Dataset of the Qinghai-Tibet Plateau (2005, 2010, 2015, 2017, and 2018) was downloaded from National Tibetan Plateau Data Center [43][44][45]. This dataset was downscaled from Land Surface Soil Moisture Dataset of SMAP Time-Expanded Daily 0.25 • × 0.25 • over the Qinghai-Tibet Plateau Area.…”
Section: Reanalysis Datasetsmentioning
confidence: 99%
“…This approach, characterized by its simplicity and accessibility, contrasts with the intricate methodologies employed by other researchers in optimizing and fusing reanalysis data. These methodologies encompass sophisticated techniques, including artificial neural networks [59], wavelet transform methods [60], genetic algorithms [61,62], and machine learning [63,64]. However, it is noteworthy that the efficacy of the aforementioned optimization is constrained to situations akin to CMADS, where certain metrics exhibit suboptimal performance relative to others.…”
Section: Optimization Of the Cmads Datasetmentioning
confidence: 99%
“…The input satellite data sources include the 16-day NDVI from MOD13A2 with 1-km spatial resolution, 8-day LAI and FPAR from the Global LAnd Surface Satellite (GLASS) with 500-m spatial resolution (Xiao et al, 2015;Xiao et al, 2014), instantaneous 1-km all-weather LST dataset (both daytime and nighttime) from the National Tibetan Plateau Data Center (Zhang et al, 2021b), and the daily SM dataset from the European Space Agency Climate Change Initiative (ESA CCI) program with 0.25-degree spatial resolution. We used a wavelet transform (WT) method provided by Hu et al (2022) combined with finer resolution satellite products (i.e., LAI, FPAR, LST) to downscale the SM dataset to 1km spatial resolution.…”
Section: Satellite and Meteorological Datasetsmentioning
confidence: 99%
“…For instance, a previous study found that the effects of topography, vegetation, precipitation, and LST greatly impact the spatial distribution of SM, resulting in large biases in the existing SM products of the TP (Liu et al, 2021). At the same time, the downscaling of coarser resolution SM products will also affect the accuracy of ET estimation (Hu et al, 2022;Sabaghy et al, 2020). Therefore, uncertainties could be inherited through errors from these input data sources.…”
Section: Uncertainties In the Et Estimation Of Hybrid Modelsmentioning
confidence: 99%